The Use Of Antiplatelet Review And Post Percutaneous Coronary Intervention In Private Hospital Surabaya - Ike Dhiah Rochmawati (Media Farmasi XXX, 2020)
Antiplatelets are medicines that stop cells in the blood (platelets) from sticking together and forming a clot, which may lead to a heart attack or stroke. Furthermore, the use of antiplatelet after percutaneous coronary intervention is one of the challenge encountered by the clinicians or hospital staff because it has to be calculated between the risk-benefit ratio. This study aims to evaluate the use of dual antiplatelet therapy in patients undergoing percutaneous coronary intervention. A retrospective study was used and data were obtained from patient records. The data obtained were analysed to know the relationship between age, gender, and type of drug combination associated with ischemic events. The patient demographics were analysed descriptively, and the comparison between age and sex group related to ischemic events was analysed using chi-square analysis. There was no statistical difference in ischemic events between age and sex group. The study reported that the most commonly used DAPT profile was the combination of Aspirin 100 mg - Clopidogrel 75 mg (38%) and Aspirin 100 mg - Ticagrelor 90 mg (28%). The profile of ischemic events in patients using the aspirin-clopidogrel combination was lower than that of the aspirin-ticagrelor combination.Keywords: Antiplatelet, Percutaneous Coronary Intervention, Coronary Heart Disease